STABILITY POLICY DURING ECONOMIC DOWNTURN: INSTITUTIONAL AND INTERVENTIONALISTIC ASPECTS - Paliulyte, Regina (Ekonomika, 2010)
The issue of stable policy became extremely relevant during the recession. Stable policy encompasses recovery of the lost equilibrium, prevention of the undesirable situation and assurance of sustainable economic development. Two competitive decisions of stable policy – intervention and institutional – can be accentuated. Intervention strategy means supply stimulation and balance recovery through fiscal and monetary policy. Institutional stable policy stresses the prevention of unwanted situations through creating a resilient institutional economic structure and freeing the market self-regulation mechanism. The article compares both strategies, analyzes their consequences, influence on the development and depth of the crisis, and possibilities of the national adaptation mechanism.